2013
DOI: 10.1007/s00421-013-2676-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single, open-sea, air scuba dive on human micro- and macrovascular function

Abstract: There appears to be a reduction in endothelium-dependent and endothelium-independent, macro- and microvascular function associated with diving. Our results suggest that in the process of vascular dysfunction during diving, functional changes in the vessel wall may not be limited to the endothelium and may be mediated by alterations in vascular smooth muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
40
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 42 publications
7
40
1
Order By: Relevance
“…With senescence the cardiovascular system undergoes complex structural and functional changes (Ardestani et al, 2015 F o r P e e r R e v i e w O n l y ). Diving too may lead to vascular dysfunction and endothelial cell death (Lambrechts et al, 2013, Wang et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With senescence the cardiovascular system undergoes complex structural and functional changes (Ardestani et al, 2015 F o r P e e r R e v i e w O n l y ). Diving too may lead to vascular dysfunction and endothelial cell death (Lambrechts et al, 2013, Wang et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In a French study of 200 professional divers (mean age 38 years), 2.5% had a high 10-year risk and 34% had an intermediate 10-year risk of an acute coronary event (Pougnet et al, 2012). Diving too may lead to vascular dysfunction and endothelial cell death (Lambrechts et al, 2013, Wang et al, 2014. Obad et al found that post-dive flowmediated dilation of the brachial artery in divers remained reduced for two days after a single air dive (Obad et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A common research approach in the physiopathology of DCS is based on the endothelial dysfunction hypothesis, which states that diving induces an alteration of endothelial cell activity, which could be a causative factor for DCS (17). In support to this, decreased vasodilation is well documented to occur in conductance arteries after diving (3,14,19,22).…”
mentioning
confidence: 95%
“…Indeed, postdive flow-mediated vasodilation (FMD) inhibition is directly linked to the oxygen fraction during SCUBA dives (19). However, hyperbaric hyperoxia (pure oxygen breathing under moderate ambient pressure) is unable to impair endothelial-dependant or independent vasodilation (3,14). Thus, the precise role of increased oxygen partial pressure in association with other factors of the dive remains to be determined.…”
mentioning
confidence: 98%
See 1 more Smart Citation